Effect of adolescent pregnancy on the incidence of low birthweight in Dr Soetomo Hospital, Surabaya, Indonesia - Nur Lailatul Fadhilah; Rizky Pranadyan (Universitas Airlangga, 2020)
Objective: The aim of this study to analyze correlation of neonatal outcome in adolescent pregnancy in Soetomo Hospital within 2014-2017.Materials and Methods: This study was analytic observational cross-sectional study using medical record period 2014-2017 in Obstetric and Gynecology Department, Faculty of Medicine of Airlangga University by using total sampling.Results: The number of total sample among all adolescent pregnancy during 4 years was 184 patient (3,2%) of 5770 patient. The neonatal outcome among all of them were low birth weight, 184 cases (7,8%) of 2350 cases were LBW. 19 cases (5,7%) of 329 cases in percentile <10. This data was analyzed by chi-square SPSS with p value 0,218 (p>0,05), means there were no significant correlation.Conclusion: Adolescent pregnancy had no correlation with low birth weight in neonatal outcome.